2015
DOI: 10.1080/13607863.2015.1050995
|View full text |Cite
|
Sign up to set email alerts
|

Age differences among older adults in the use of emotion regulation strategies. What happens among over 85s and centenarians?

Abstract: Age differences were observed in the use of emotion regulation strategies, with older age groups using proactive strategies less and passive strategies more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…However, they might become motivated to use suppression later in life to avoid engaging with intense stressors (e.g., poor health; Charles, 2010). Some indirect evidence for this hypothesis comes from a study where adults 85 years and older reported regulating their emotions in more passive ways (e.g., suppressing one’s emotions, avoiding the problem) than adults ages 65–84 (Etxeberria, Etxebarria, Urdaneta, & Yanguas, 2016). Thus, people may only decrease in their suppression up until early old age then increase in late old age.…”
Section: Past Findings On Emotion Regulation Strategy Use Across Adul...mentioning
confidence: 99%
“…However, they might become motivated to use suppression later in life to avoid engaging with intense stressors (e.g., poor health; Charles, 2010). Some indirect evidence for this hypothesis comes from a study where adults 85 years and older reported regulating their emotions in more passive ways (e.g., suppressing one’s emotions, avoiding the problem) than adults ages 65–84 (Etxeberria, Etxebarria, Urdaneta, & Yanguas, 2016). Thus, people may only decrease in their suppression up until early old age then increase in late old age.…”
Section: Past Findings On Emotion Regulation Strategy Use Across Adul...mentioning
confidence: 99%
“…As to the habitual use of emotion regulation strategies, a study conducted by Etxeberria et al (2016) suggests that very old adults, as compared with young old adults, use proactive and problem-solving strategies less (e.g., venting one's emotions, confronting the source of the problem, seeking social support). However, very old individuals used so-called passive strategies such as accepting the problem, avoiding the problem, and suppressing one's feelings more often.…”
Section: Age Differences Within Old and Very Old Age: Empirical Evidencementioning
confidence: 99%
“…With regard to the two broad sets of emotion regulation strategies (antecedent-focused and response-focused), one overarching theme in the aging literature is that older adults prefer more passive, antecedent-focused strategies that do not involve direct confrontation with emotion generating stimuli, such that use of proactive, response-focused strategies involving direct confrontation of negative emotions declines with age (Blanchard-Fields, Stein, & Watson, 2004;Etxeberria, Etxebarria, Urdaneta, & Yanguas, 2016;Lipovcan, Prizmic, & Franc, 2009;Scheibe et al, 2015;Yeung, Fung, & Kam, 2012). Given that the ability to effectively use proactive strategies is believed to decline in late adulthood, adopting use of passive strategies may compensate for shifts in available cognitive resources (Heckhausen, 2006;Urry & Gross, 2010).…”
Section: Aging and Emotion Regulation Strategy Usementioning
confidence: 99%